Proses Pengembangan Berpikir Kritis Siswa Melalui Problem Based Learning Pada Pembelajaran Pai Di Ma Nurul Jadid - Ali Samsi; Dwi Cahyo Utomo (Universitas Pakuan, 2026)
The Process of Developing Students' Critical Thinking through Problem Based Learning in Pai Learning at Ma Nurul Jadid The purpose of this study is to describe the process of how students' critical thinking skills develop through the application of Problem Based Learning (PBL) in Islamic Religious Education (PAI) learning at MA Nurul Jadid and identify the role of teachers and the factors that influence these developments. The research applied a qualitative approach with a single case study design. Data collection was carried out through classroom observations, semi-structural interviews with teachers, students, and curriculum leaders, as well as documentation analysis (lesson plans, worksheets, student products, learning recordings). The analysis follows the Miles and Huberman model (reduction, presentation, verification) which is equipped with confidence-building efforts in the form of triangulation, member checks, and trail audits. The findings suggest that PBL provides a framework for critical thinking processes—from identifying problems to constructing arguments—but these developments are uneven. This inconsistency is influenced by group dynamics, individual social capital (e.g., confidence and verbal ability), inconsistent teacher facilitation practices, and the absence of operational critical thinking indicator assessments. The role of teachers as facilitators has proven to be crucial; Planned interventions can increase participation, but require more systematic scaffolding and role setting. The practical implications of the research include the need to improve teacher facilitation competence, the preparation of a rubric for measurable critical thinking assessments, and the design of graded cognitive tasks to strengthen the effectiveness of PBL in the context of pesantren. Follow-up research recommendations include facilitation intervention tests and assessments in several madrasas as well as quantitative comparative studies.